Differences in the Results of the Evaluation of Special Program Implementation at Two Special Schools in the City of Banjarmasin - Utomo, Utomo; Thaibah, Hayatun; Nuzula, Muhammad Firdaus; Almua’arif, Nuril Shafira (Department of Special Education, 2023)
The evaluation obtained depends on the objectives of the evaluation program it self which of course have been formulated previously and are accounted for in the form of a program, to reward program implementers, for selection and promotion, for program improvement, and to predict the possibility of continuing the program in the future. This research is to find out the differences in the evaluation results of 2 Special Public Schools in the City of Banjarmasin, Indonesia. This type of research approach is to use a quantitative approach. The data collection technique was through a questionnaire accompanied by free interviews addressed to several teachers and the principal. The subjects of the study were 33 people, with details at the Pelambuan State Special School in Banjarmasin as many as 16 people and 17 people at the Public Special School 2 Banjarmasin City. The results of the data were analyzed using independent sample t test. The value of t count is 1.120 < t table is 2.040, then based on the basis of decision making through a comparison of the t count value with t table, it can be concluded that there is no difference in the average results of the evaluation of the implementation of special programs at the Pelambuan Banjarmasin State Special School and the Public Special School 2 Banjarmasin.